PENGARUH EKSTRAK ETANOL BUAH KETUMBAR( COLOANDRUMSATIVUM L.) DALAM MENGATASI KELELAHAN PADA MENCIT PUTIH (MUS MUSCULUS L.) GALUR DDY - Marbun, Nelson (E-Journal Widya Kesehatan dan Lingkungan, 2005)
Coriander fruits (Coriandrum sativum L.) contains active compounds capable of stimulatory effect. Moreover, ethanol ectract of coriander (Coriandrum sativum L.) fruits has caffeine- like activity. This active compound is aromatic oil and flavonoid. This study has been performed to obtain information on the effect of ethanol extract cotiander fruits (Coriandrum sativa L.) on decreasing fatigue. The study was conducted by employing a complete random design on male white mice (age 10-12 weeks, 20-35 g). The method was a swim test with ballast. The Stimulant effect was compared to a standard caffeine 50 mg/kg BW effect , and ethanol extract coriander fruits (Coriandrum sativum L.) of 7.5% w/v, 10% w/v, 12.5% w/v concentrations, and using aquadest as control. The result of each group were compared and analyzed using Kolmogorov-Smirnov and Levene tests to determine normality and homogeneity of result, and ANOVAÂ parametric method. There was a significant difference between each group using Tukey method. The result showed that ethanol extract coriander fruits (Coriandrum sativum L.) was significantly different between each group, and ethanol extract coriander fruits (Coriandrum sativum L.) had a stimulant effect and capable of decreasing fatigure.